Le fado et la dictature : les figures de la « victime » - Agnès Pellerin (Centre de Recherches sur les Mondes Américains, 2015)
Today, forty years after the end of the Estado novo (1926-1974) in Portugal, the fado, performed by a solo singer accompanied by guitars, is ever considered, in the collective Portuguese imaginary, as a natural accomplice of this dictatorship. However, this popular spontaneous song, considered during a long time as a « subculture », suffered during this period violations of his freedom of expression. Fado paradoxically knows a mass diffusion and the power considered it as an easy tool of propaganda. But the fact that the fado has been looked as an active symbol of a reactionary ideology hide the censorship he suffered and enclosed it in a limited interpretative frame that shows the complexity of the Portuguese democratic transition. Due to his poem topics (realistic picture of the “sadness” of life), fado crystallized the idea of a human « resignation », and turned scapegoat, as opposed to the “protest song”, defending liberty, born in the 1960’s. Showing us that the status of victim requires, first of all, a social legitimacy.